2022
DOI: 10.1002/jmv.28073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the clinical and epidemiological characteristics of human influenza virus versus human respiratory syncytial virus versus human metapneumovirus infection in nine provinces of China during 2009−2021

Abstract: A comparative analysis of confirmed cases of human influenza virus (HIFV), human respiratory syncytial virus (HRSV), and human metapneumovirus (HMPV) was conducted to describe their clinical and epidemiological characteristics. During 2009−2021, active surveillance of acute respiratory infections (ARIs) was performed in nine provinces of China. Clinical and epidemiological information and laboratory testing results of HIFV, HRSV, and HMPV were analyzed. Among 11591 ARI patients, the single-infection rates of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(100 reference statements)
2
16
0
Order By: Relevance
“…The proportion of ARI patients with clinical symptoms decreased after COVID-19, which may be related to the decreased positive rates of viral and bacterial infections after COVID-19. Previous studies have shown that HMPV infection or coinfection with HMPV and other respiratory viruses increases the risk of pneumonia and severe clinical symptoms [ 6 ]. In addition, coinfections with respiratory pathogens also increase the risk and severity of clinical symptoms in ARI patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of ARI patients with clinical symptoms decreased after COVID-19, which may be related to the decreased positive rates of viral and bacterial infections after COVID-19. Previous studies have shown that HMPV infection or coinfection with HMPV and other respiratory viruses increases the risk of pneumonia and severe clinical symptoms [ 6 ]. In addition, coinfections with respiratory pathogens also increase the risk and severity of clinical symptoms in ARI patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, coinfections with respiratory pathogens also increase the risk and severity of clinical symptoms in ARI patients [ 17 ]. Thus, the decrease in the positive rate of respiratory pathogens after COVID-19 has caused a decrease in the proportion of ARI patients with clinical symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates based on a systematic review of published data report 109.5 million influenza episodes annually only in children under five years of age [ 1 , 2 , 3 ]. Influenza undergoes seasonal fluctuations with regards to its frequency, although during the SARS-CoV-2 pandemic, the previously known seasonal patterns were altered in various regions, mainly due to nonpharmaceutical interventions [ 4 , 5 ]. The most important preventive measure, influenza vaccination, is globally available.…”
Section: Introductionmentioning
confidence: 99%